LncRNA HOX transcript antisense RNA mediates hyperglycemic‐induced injury in the renal tubular epithelial cell via the miR‐126‐5pAkt axis - Qiong Jiang; Ting Yang; Yan Zou; Mingjie He; Qingchun Li; Xiaohui Chen; Aimin Zhong (Aging Medicine, 2023)
Abstract Objective: To investigate the involvement of HOX transcript antisense RNA (HOTAIR) in the injury of renal tubular epithelial cells induced by high glucose. Results: In high glucose‐induced HK‐2 cells, the expression of HOTAIR was upregulated, resulting in suppressed cell proliferation. Meanwhile, HOTAIR upregulates the expression of pro‐apoptotic proteins Bax and cleaved caspase‐3, while downregulating the expression of the anti‐apoptotic protein Bcl‐2. Luciferase reporter assays revealed that HOTAIR could target miR‐126‐5p. Additionally, it was found that the PI3K/Akt signaling pathway serves as a downstream target of miR‐126‐5p. Knockdown of HOTAIR relieved apoptosis, whereas further inhibition of miR‐126‐5p led to apoptosis in HK‐2 cells. Conclusions: HOTAIR plays a regulatory role in mediating high glucose‐induced injuries in HK‐2 cells, specifically affecting apoptosis and cell viability, via the miR‐126‐5p/PI3K/Akt signaling pathway.